Surgery in the Digital Era: Traversing Advancements, Challenges and Future Frontiers - Fahad Umer; Sana Zeeshan; Saleem Islam (Journal of the Pakistan Medical Association, 2024)
In the ever-evolving world of modern healthcare, the incorporation of cutting-edge technologies has ushered surgical treatments into a new era.r This editorial digs into the disruptive influence of technical breakthroughs, specifically the merger of robots and Artificial Intelligence (AI) in the surgical scene of Pakistan. Furthermore, it investigates the potential of telemedicine to overcome healthcare gaps in rural or disadvantaged locations, while also addressing ethical considerations, implementation challenges, and future prospects. The digital era has brought about a paradigm shift in surgical methods, with robotics and AI taking centre stage. Surgical robots, led by precise algorithms and realtime data analysis, have transformed the accuracy and efficiency of surgeries. These tools allow surgeons to conduct complex surgical procedures with more precision, potentially lowering the risk of errors ultimately improving patient outcomes.1